Unconventional activation of PRKDC by TNF-α: deciphering its crucial role in Th1-mediated inflammation beyond DNA repair as part of the DNA-PK complex - Mohamed A. Ghonim; Jihang Ju; Kusma Pyakurel; Salome V. Ibba; Mai M. Abouzeid; Hamada F. Rady; Shigemi Matsuyama; Luis Del Valle; A. Hamid Boulares (BMC, 2024)
Abstract Background The DNA-dependent protein kinase (DNA-PK) complex comprises a catalytic (PRKDC) and two requisite DNA-binding (Ku70/Ku80) subunits. The role of the complex in repairing double-stranded DNA breaks (DSBs) is established, but its role in inflammation, as a complex or individual subunits, remains elusive. While only ~ 1% of PRKDC is necessary for DNA repair, we reported that partial inhibition blocks asthma in mice without causing SCID. Methods We investigated the central role of PRKDC in inflammation and its potential association with DNA repair. We also elucidated the relationship between inflammatory cytokines (e.g., TNF-α) and PRKDC by analyzing its connections to inflammatory kinases. Human cell lines, primary human endothelial cells, and mouse fibroblasts were used to conduct the in vitro studies. For animal studies, LPS- and oxazolone-induced mouse models of acute lung injury (ALI) and delayed-type hypersensitivity (DHT) were used. Wild-type, PRKDC+/−, or Ku70+/− mice used in this study. Results A ~ 50% reduction in PRKDC markedly blocked TNF-α-induced expression of inflammatory factors (e.g., ICAM-1/VCAM-1). PRKDC regulates Th1-mediated inflammation, such as DHT and ALI, and its role is highly sensitive to inhibition achieved by gene heterozygosity or pharmacologically. In endothelial or epithelial cells, TNF-α promoted rapid PRKDC phosphorylation in a fashion resembling that induced by, but independent of, DSBs. Ku70 heterozygosity exerted little to no effect on ALI in mice, and whatever effect it had was associated with a specific increase in MCP-1 in the lungs and systemically. While Ku70 knockout blocked VP-16-induced PRKDC phosphorylation, it did not prevent TNF-α − induced phosphorylation of the kinase, suggesting Ku70 dispensability. Immunoprecipitation studies revealed that PRKDC transiently interacts with p38MAPK. Inhibition of p38MAPK blocked TNF-α-induced PRKDC phosphorylation. Direct phosphorylation of PRKDC by p38MAPK was demonstrated using a cell-free system. Conclusions This study presents compelling evidence that PRKDC functions independently of the DNA-PK complex, emphasizing its central role in Th1-mediated inflammation. The distinct functionality of PRKDC as an individual enzyme, its remarkable sensitivity to inhibition, and its phosphorylation by p38MAPK offer promising therapeutic opportunities to mitigate inflammation while sparing DNA repair processes. These findings expand our understanding of PRKDC biology and open new avenues for targeted anti-inflammatory interventions.